2017
DOI: 10.1007/s40846-016-0203-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of New Biphasic Calcium Phosphate Bone Substitute: Rabbit Femur Defect Model and Preliminary Clinical Results

Abstract: Autogenous bone grafting, used to repair bone defects, is limited and the donor site can experience complications. Compared to autogenous bone graft, artificial bones have different porosity, which might make them suitable alternatives to bone grafts. Here, two porous biphasic calcium phosphate bone substitutes, namely Bicera™ and Triosite™, are used in an animal study and clinical practice to find a suitable porosity for implantation. Bicera™ and Triosite™ consist of 60 wt% hydroxyapatite and 40 wt% β-tricalc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 19 publications
(18 reference statements)
4
23
0
1
Order By: Relevance
“…[57][58][59] For instance, the bone remodeling rates were quantitatively measured and the rates of 1.0 to 1.5 mm/day, 1.2 to 1.5 mm/day, and 1.5 to 2.0 mm/day reported for in humans, mini-pigs, and dogs, respectively. 47 Our results further showed that the bone mineralization surfaces (sLS/BS) at weeks 4 or 8 were different for the two grafted materials. 61 Similar to our results, the osteoinductive potential of a synthetic biphasic calcium phosphate bone graft has recently been suggested to be based on the findings of new bone formation noted in vitro and sub-cutaneous implantation.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…[57][58][59] For instance, the bone remodeling rates were quantitatively measured and the rates of 1.0 to 1.5 mm/day, 1.2 to 1.5 mm/day, and 1.5 to 2.0 mm/day reported for in humans, mini-pigs, and dogs, respectively. 47 Our results further showed that the bone mineralization surfaces (sLS/BS) at weeks 4 or 8 were different for the two grafted materials. 61 Similar to our results, the osteoinductive potential of a synthetic biphasic calcium phosphate bone graft has recently been suggested to be based on the findings of new bone formation noted in vitro and sub-cutaneous implantation.…”
Section: Discussionsupporting
confidence: 55%
“…43 Although the ideal ratio of HA to -TCP is still under investigation, [44][45][46] variant ratios of BCPs have been widely used for bone graft substitutes, with favorable results A review of the commercially available BCP indicated that the most common ratio is 60% HA and 40% -TCP. 47 One of the most used DBBMs for various augmentation procedures 15 was also selected in this study. 47 One of the most used DBBMs for various augmentation procedures 15 was also selected in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, chitosan/β‐tricalcium phosphate (Chi/TCP) scaffold promoted bone regeneration of tibial defects in rabbit . Other composites such as alginate/hydroxyapatite, hydroxyapatite/gelatin nanocomposite, and biphasic calcium phosphate scaffolds have been used to enhance new bone formation. However, the majority of these materials and composites are osteoconductive and exhibit inadequate osteoinductivity for clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, optimal methods for the treatment of segmental bone defects, particularly weight‐bearing bone defects, are still sought. β‐TCP has been widely used as a scaffold for small bone defects due to its good osteoconductivity, but its clinical use is limited due to its rapid degradation rate and poor mechanical strength . Recently, bioglass has received growing attention because of its superior mechanical properties .…”
Section: Introductionmentioning
confidence: 99%